DNA barcoding and species delimitation of Chaitophorinae (Hemiptera, Aphididae) - Xi-Chao Zhu; Jing Chen; Rui Chen; Li-Yun Jiang; Ge-Xia Qiao (ZooKeys, 2017)
Chaitophorinae aphids are widespread across Eurasia and North America, and include some important agricultural and horticultural pests. So, accurate rapid species identification is very important. Here, we used three mitochondrial genes and one endosymbiont gene to calculate and analyze the genetic distances within different datasets. For species delimitation, two distance-based methods were employed, threshold with NJ (neighbor-joining) and ABGD (Automatic Barcode Gap Discovery), and two tree-based approaches, GMYC (General Mixed Yule Coalescent) and PTP (Poisson Tree Process). The genetic interspecific divergence was clearly larger than the intraspecific divergence for four molecular markers. COI and COII genes were found to be more suitable for Chaitophorinae DNA barcoding. For species delimitation, at least one distance-based method combined with one tree-based method would be preferable. Based on the data for Chaitophorus saliniger and Laingia psammae, DNA barcoding may also reveal geographical variation.